Comparing the Structural and Physicochemical Properties of Highland Barley β-Glucan from Different Sources: A Focus on Color - Ping Yu; Xuemin Kang; Pengfei Liu; Zhengzong Wu; Yue Cheng; Bo Cui; Wei Gao (Foods)
Herein, β-glucan (BG) was extracted from different colored varieties of highland barley (HB, Hordeum vulgare), defined as BBG, WBG, and LBG depending on the colors of black, white, and blue and their molecular structure and physicochemical properties were investigated through a series of technical methods. The high-performance anion-exchange chromatography (HPAEC) results indicated the extracted BBG, LBG, and WBG mainly comprised glucose regardless of color. The molecular weight (Mw) of BBG, LBG, and WBG were 55.87 kDa, 65.19 kDa, and 81.59 kDa, respectively. 4-Glc(p), 3-Glc(p), and t-Glc(p) accounted for a larger proportion (>90%) of the total methylated residues according to gas chromatography–mass spectrometry (GC-MS) analysis. Additionally, Fourier transform infrared (FT-IR) spectroscopy revealed that the β-linkage of LBG had a greater capacity to develop stronger hydrogen bonds, due to the absence of 3,4-Glc(p). Among them, LBG had a low particle size distribution and a high shear viscosity, showing obvious round aggregates on its surface. Meanwhile, BBG presented a high peak viscosity (PV) and thermal stability. Based on the differences in their molecular structure, it could be concluded that there were different physicochemical properties among BBG, LBG, and WBG.